Diagnostic Significance of Z-Score in Echocardiography in Children with Congenital Heart Defects (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2026)
Congenital heart defects (CHD) are among the most common cardiovascular disorders in children. Continuous growth and somatic variability in pediatric patients limit the diagnostic accuracy of absolute echocardiographic measurements, highlighting the importance of standardized Z-score assessment.